Kinematic analysis of the preparatory and takeoff motion in the long jump - Muraki, Y.; Koyama, H.; Ae, M. (ISB Congress, 2005)
The purposes of this study were to investigate motion variability of the preparatory and takeoff motions for skilled long jumpers and to compare their motions between different approach velocity groups.